Synthetic Strategies for Variably Substituted Ruthenium–Imidazophenanthrolinium Complexes (Eur. J. Inorg. Chem. 5/2015). Issue 5 (February 2015) - Petermann, Lydia; Staehle, Robert; Pilz, T. David; Sorsche, Dieter; Görls, Helmar; Rau, Sven
Abstract : The cover picture shows a mechanic who forms ruthenium complexes consisting of an imidazophenanthrolinium ligand that contains an NHC (N‐heterocyclic carbene) precursor moiety to introduce a second metal center. Eminently, he can introduce any small or sterically demanding alkyl substituent on the imidazo‐N without influencing the outstanding photophysical properties. Therefore, our compounds are excellent chromophores. In future applications in light‐driven catalysis, the different substituents will be important after connection of a second metal center by sterically influencing the catalytic unit. Details are discussed in the article by S. Rau et al. onp. 750 ff . For more on the story behind the cover research, see theCover Profile .